Barriers effecting successful implementation of E-learning in Saudi Arabian universities - Naveed, Quadri Noorulhasan; Muhammed, Abulhafeez; Sanober, Sumaya; N. Qureshi, Mohamed Rafik; Shah, Asadullah (International Association of Online Engineering, 2017)
advancement of digital technology is influencing the leaping development of various activities in our daily life. E-learning systems has also gained a competitive edge over the prevailing traditional methodology. The prevailing pedagogy is being replaced by the E-learning teaching systems. E-Learning, teaching learning methodology provides more flexibility and allows freedom from time, place, physical presence, hectic, and stressful teaching-learning etc, thus play a vital role in education system. However, there are many barriers in E-Learning methodology for successful teaching-learning. Present research paper attempts to study the various barriers that are affecting the successful implementation of E-Learning in Saudi Arabian Universities. This study reviews various barriers from literature and identified most important E-Learning barriers which are described and grouped in four dimensions such as student, instructor, infrastructure and technology, and institutional management. Sixteen barriers falling under these relevant dimension were validated their importance quantitatively through university students, instructors, and E-Learning staffs of some well known universities in Saudi-Arabia. A survey instrument was developed and tested on a sample of 257 respondents of Saudi Arabian Universities. It was found that infrastructure and technology dimension is the most significant as perceived by respondents. Results of the study also reveal that, all barrier factors are highly reliable, therefore should be taken care for successful implementation of E-learning systems.